Environmental Advantages of Renewable Energy: A Review - Savita Chhipekar; Aniket Vishwkarma; Shyamkali Ahirwar; Nikhil Nagar (International Journal of Environmental Noise and Pollution Control, 2023)
There is a shortage of fuel in many emerging nations, including India, because of increased manufacturing for many different development initiatives. If the thermal energy sources used to meet this rise in demand are coal-based, environmental damage and high production costs ensue. So, the greatest alternative approach is for the nation to build renewable energy-based power facilities. Sustainable in light of current and future societal, economic, and social demands, renewable technologies are regarded as clean sources that minimise adverse environmental consequences and create the least secondary waste. The sun's rays, the most prevalent source of electricity, can be used directly or indirectly. There is a lot of potential to use the solar energy that is now accessible for temperature uses like cooking, water heating, and crop drying. A mature, competitive, and essentially pollution-free technology, wind energy is used extensively throughout much of the world to generate electricity. Additionally, the viability of gasification has been established, making it a potential technology. By displacing traditional energy sources, renewable energy technologies provide a great opportunity to reduce greenhouse gas emissions and halt global warming. It has been among the most successful models to produce clean, environmentally friendly, cost-effective energy and has numerous advantages. For the sake of long-term growth, this article discusses several types of renewable energy sources and their good and negative effects on the environment.
Keywords: Resources, Environment, Renewable, solar; Wind, Sustainable; energy